A Review of Biochar Based Technologies in Carbon Capture and Sequestration - Neema, Paragi; Narang, Mridul; Mann, Harmann Singh (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 5 No 4 (2018): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
The emission of greenhouse gases, predominantly, carbon dioxide, due to burning, decomposition and various other ways to dispose of agricultural crop residues or biomass waste has led to an increased persistence of carbon dioxide in the atmosphere. Biochar is biologically active charcoal which is created by biomass feedstock pyrolysis in an oxygen deprived condition. Feedstock such as manure generated by poultry and livestock operations, agricultural waste and biodegradable solid waste can be used for the production of biochar. Biochar can be used as a soil amendment for poor soils, carrier for plant nutrients, water filtering medium, insulation in the building industry and as carbon sinks due to its porosity, stability and high surface area. The pyrolysis of biomass in the absence of oxygen yields an array of solid (biochar - dominant product during slow pyrolysis), liquid (bio-oil) and gaseous (syngas) products. As the key element in a new arbon-negative strategy, biochar can mitigate climate change by carbon sequestration and facilitate the development of a sustainable society by resolving critical challenges of food and energy security, etc. This review emphasizes on biochar utility as an approach to carbon capture and sequestration and hence the need to develop a carbon negative industry by minimizing atmospheric carbon. How to cite this article: Neema P, Narang M, Mann HS. A Review of Biochar Based Technologies in Carbon Capture and Sequestration. J Adv Res Alt Energ Env Eco 2018; 5(4): 33-38. DOI: https://doi.org/10.24321/2455.3093.201806